The logic of piloting and trans-border regionalism: The project-oriented approach in EU-Russian cooperation - Andrey Makarychev; Sergei Prozorov (Danish Institute for International Studies (DIIS), 2004)
This paper addresses the impact of innovative developments in Russian policy-making discourse during the Putin presidency on the transformation of conflict issues in EU-Russian relations. The increasing recourse of Russian policy-makers in the border regions to the so-called `projectoriented approach', which has an affinity to the modality of policy-making espoused by the EU programmes in Russia, has important consequences for conflictual dispositions in EU-Russian trans-border relations.
Keywords: 330; Internationale Zusammenarbeit; EU-Staaten; Russland